STUDYING THE ABILITY OF “AUTOMOBILE – DRIVER – ROAD” SYSTEM TO BYPASS A SUDDEN OBSTACLE - Ostashevskiy, Serhiy (Scientific Works of Vinnytsia National Technical University, 2015)
The paper estimates the factors required to organize driving training on bypassing a sudden obstacle. The automobile characteristics are determined as well as control actions of the driver required to successfully bypass a sudden obstacle. Besides, a possibility of successful evaluation of the learning progress and driver’s performance is determined on the basis of transient characteristics of the “automobile – driver – road” system. REFERENCES 1. Автотранспортные средства. Управляемость и устойчивость. Технические требования. Методы испытаний. ГОСТ 31507:2012. – [Действующий от 2013-09-01]. – М. : Стандартинформ, 2012. – 51 с. – (Межгосударственный стандарт). 2. Осташевский С. А. Обоснование разработки экзоскелетальной модели управления автомобилем / С. А. Осташевский // Автошляховик України. – 2013. – № 2. – С. 10 – 13. 3. Поліщук В. П. Колебательная устойчивость автомобиля / В. П. Поліщук, С. А. Осташевський // Сучасні технології та перспективи розвитку автомобільного транспорту: зб. наук. праць за матеріалами VI між нар. наук.-прак. конф., 21 – 23 жовт. 2013 р. – М-во освіти і науки України, Вінниц. націон. техн. ун-т [та інш.]. – Вінниця: ВНТУ, 2013. – С. 36 – 37. 4. Литвинов А. С. Управляемость и устойчивость автомобиля / Литвинов А. С. – М. : Машиностроение, 1971. – 416 с.